Pengaruh Social Media Digital Marketing dan Word Of Mouth Terhadap Keputusan Pembelian Produk Sublonto.Co di Sukawati Gianyar - Winata, I Kadek Sukma; Widani Sugianingrat, I A; Suasthi Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Purchasing decisions are a major part of consumer behavior in buying products. Purchase decisions are influenced by many factors including social media marketing and word of mouth. The formulation of the research problem is how the influence of social media marketing and word of mouth partially and simultaneously on purchasing decisions. The purpose of this study was to determine the effect of social media marketing and word of mouth partially and simultaneously on purchasing decisions. Research location in Sublonto.Co. The sample used was 98 respondents. Methods of data collection in this study using observation, interviews and questionnaires. In this data analysis technique Instrument Tests are carried out by Testing Validity, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t-test and F-test. Based on the results of the study, it was found that social media marketing had a significant positive effect on purchasing decisions, word of mouth had a significant positive effect on purchasing decisions and simultaneously social media marketing and word of mouth had a significant effect on purchasing decisions. The magnitude of the influence of word of mouth on purchasing decisions is 54.4%. Suggestions in this study are that Sublonto.Co is expected to increase the intensity of promotion on social media, provide complete and up-to-date information on profiles on social media, always offer quality products and according to consumer needs and continue to innovate on the products offered.